A 4D view on insulin secretory granule turnover in the ß-cell - Müller, A.; Mziaut, H.; Neukam, M.; Knoch, K.; Solimena, Michele (2017)
© 2017 John Wiley & Sons Ltd Insulin secretory granule (SG) turnover consists of several highly regulated processes allowing for proper ß-cell function and insulin secretion. Besides the spatial distribution of insulin SGs, their age has great impact on the likelihood of their secretion and their behaviour within the ß-cell. While quantitative measurements performed decades ago demonstrated the preferential secretion of young insulin, new experimental approaches aim to investigate insulin ageing at the granular level. Live-cell imaging, automated image analysis and correlative light and electron microscopy have fostered knowledge of age-defined insulin SG dynamics, their interaction with the cytoskeleton and ultrastructural features. Here, we review our recent work in regards to the connection between insulin SG age, SG dynamics, intracellular location and interaction with other proteins.